The Effect of Moringa Oleifera Leaves on Increasing Breast Milk Production in Postpartum Mothers: A Scoping Review - Titin Sundari nazara (JOURNAL EDUCATIONAL OF NURSING(JEN), 2025)
Moringa leaves are a very promising local food ingredient to be processed into dishes for postpartum mothers. This is because moringa contains phytosterol compounds which are known to increase and facilitate breast milk production. A scoping review was conducted with the primary aim of investigating the extent to which moringa leaves influence the increase in breast milk production in mothers after childbirth. This study only included articles that presented quantitative evidence regarding the effect of moringa leaves on increasing breast milk. In its execution, this review utilized the scoping review method, a technique that functions to map all relevant literature in a research field. The results of the review revealed that regular consumption of moringa leaves, in any form, has significant potential to increase breast milk production in nursing mothers, thus ensuring an adequate breast milk supply.Keywords: Moringa Oleifera, Breast Milk production